1994
DOI: 10.1007/bf00700635
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a dimethylsulfide-utilizingHyphomicrobium species and its application in biofiltration of polluted air

Abstract: The methylotrophic bacterium Hyphomicrobium VS was enriched and isolated, using activated sewage sludge as inoculum in mineral medium containing dimethylsulfide (DMS) at a low concentration to prevent toxicity. DMS concentrations above 1 mM proved to be growth inhibiting. Hyphomicrobium VS could use DMS, dimethylsulfoxide (DMSO), methanol, formaldehyde, formate, and methylated amines as carbon and energy source. Carbon was assimilated via the serine pathway. DMS-grown cells respired sulfide, thiosulfate, metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 27 publications
2
43
2
Order By: Relevance
“…Results revealed that only Hyphomicrobium strains were able to grow using the three substrates individually as the only carbon and energy source, similar to results of previous studies (De Bont et al 1981;Pol et al 1994). The other isolates grew on methanol as their sole carbon and energy source, but were unable to grow on DMS and DMSO.…”
Section: Methylotrophic Bacteria Isolated From the Enrichment Culturessupporting
confidence: 88%
“…Results revealed that only Hyphomicrobium strains were able to grow using the three substrates individually as the only carbon and energy source, similar to results of previous studies (De Bont et al 1981;Pol et al 1994). The other isolates grew on methanol as their sole carbon and energy source, but were unable to grow on DMS and DMSO.…”
Section: Methylotrophic Bacteria Isolated From the Enrichment Culturessupporting
confidence: 88%
“…Both aerobic and anaerobic DMS-degrading microorganisms have been previously described. Aerobic DMS-degrading microorganisms that have been previously isolated from sewage treatment plants, marine sediments, soil and biofilters include Thiobacilli (De Zwart and Kuenen, 1992;Visscher and Taylor, 1993), Hyphomicrobia (Suylen and Kuenen, 1986;Pol et al, 1994) and Methylophaga (De Zwart et al, 1996). Anaerobic DMS-degrading bacteria previously described are methanogens (Kiene et al, 1986;Lomans et al, 1999b), anoxygenic phototrophs (Widdel and Pfennig, 1981;Zeyer et al, 1987), sulfate-reducing bacteria (Tanimoto and Bak, 1994) and denitrifying bacteria (Visscher and Taylor 1993b).…”
Section: Oxidation Of Reduced Sulfur Compoundsmentioning
confidence: 99%
“…These bacteria are ubiquitous in the biosphere and have been isolated from a wide variety of natural habitats including plants, soils and freshwater and marine sediments (Anthony, 1982). Methylotrophs play an important role in biogeochemical cycling and possess a potential for use in bioremediation (Pol et al, 1994;De Marco et al, 2004). We are studying a specific habitat that is rich in methylotrophic activity: the sediment of Lake Washington at a depth of about 60 m (Kuivila et al, 1988;Costello & Lidstrom, 1999).…”
mentioning
confidence: 99%